Estimation of intake and quantification of hemoglobin adducts of acrylamide in adolescents in Sweden - Vryonidis, Efstathios; Törnqvist, Margareta; Lignell, Sanna; Rosén, Johan; Aasa, Jenny (Frontiers in Nutrition, 2024)
Blood samples (n = 600) from participants in the Swedish dietary survey Riksmaten Adolescents 2016–17 were analyzed with respect to hemoglobin (Hb) adducts from acrylamide (AA) and its metabolite glycidamide (GA) as biomarkers of internal dose/exposure. The results are presented from statistical analyses of food consumption data (2-day dietary recall and questionnaires) and measured Hb adduct levels. The estimated exposure as well as consumption data were examined in relation to non-dietary factors such as sex, age (group medians of 12, 15, and 18 years), place of residence (urban/rural), smoking status, and parental education level. The median AA adduct level was estimated to be 34 pmol/g Hb (range 14–225). No significant difference was found for place of residence, parental education, sex, or age. A significant difference was found between the median adduct levels of daily smokers (n = 8) and never smokers (n = 323) in the older age groups, but not between occasional smokers (n = 47) and never smokers. The median differences between daily smokers and never smokers were 76, 40, and 128 pmol/g Hb for AA, GA, and AA + GA, respectively. The median AA intake for the whole group of adolescents, as estimated from dietary recall data combined with reported concentrations in food, was 0.40 μg/kg bw/day. The corresponding median intake estimated from measured Hb adduct levels of AA was 0.20 μg/kg bw/day. A significant, although low, positive Spearman correlation was found between the two intake estimates (p-value = 8 × 10−3; ρ = 0.11). From the estimated intake of AA from food frequency questionnaires, significance was found for the 15-year-old children with higher AA adduct levels observed at higher consumption frequencies of fried potatoes/French fries. AA is considered a genotoxic carcinogen. For the estimated intake of AA for any age group and method (dietary recall or AA adduct), both a calculated margin of exposure as well as lifetime quantitative cancer risk estimates indicate health concern. A future study on food consumption designed with respect to AA exposure would provide a better understanding of the correlation between consumption and exposure and should give a more reliable estimate of the contribution of dietary AA to the overall cancer risk.